PrEP distribution in pharmacies: a systematic review. Issue 2 (21st February 2022) - Kennedy, Caitlin E; Yeh, Ping Teresa; Atkins, Kaitlyn; Ferguson, Laura; Baggaley, Rachel; Narasimhan, Manjulaa
Abstract : Introduction: Novel mechanisms of service delivery are needed to expand access to pre-exposure prophylaxis (PrEP) for HIV prevention. Providing PrEP directly through pharmacies could offer an additional option for reaching potential users. Methods: We conducted a systematic review of studies examining effectiveness, values and preferences of end users and health workers, and cost of PrEP initiation and continuation through pharmacies (pharmacy access). We searched PubMed, CINAHL, LILACS and EMBASE through 2 December 2020. We also searched clinical trial registries and recent HIV conference abstracts. Standardised methods were used to search, screen and extract data from included studies. Results: No studies met the inclusion criteria for the effectiveness review, for either PrEP initiation or continuation. However, six 'case studies' presenting non-comparative data from PrEP pharmacy programmes demonstrated feasibility of this model in the USA. Eleven studies reported values and preferences of end users and health workers. In the USA, Kenya and South Africa, potential PrEP clients generally supported pharmacy access, although some preferred clinics. One study of PrEP pharmacy clients found all would 'definitely recommend' the programme. Six studies found pharmacists were generally supportive of offering PrEP; one study including doctors found more limited favour, while one study of diverse Kenyan stakeholders found broad support. Three studies reported cost data indicating client willingness to pay in the USA and Kenya and initial sustainability of a clinic financial model in the USA. Conclusion: Provision of PrEP through pharmacies has been demonstrated to be feasible in the USA and acceptable to potential end users and stakeholders in multiple settings. Limited evidence on effectiveness and requirements for laboratory testing and assurance of high-quality services may limit enthusiasm for this approach. Further research is needed to determine if pharmacy access is a safe and effective way to help achieve global HIV prevention goals. PROSPERO registration number: CRD42021231650.